DEGRADATION RATES OF ORGANIC PHOSPHORUS IN LAKE SEDIMENT - Reitzel K.; Ahlgren J.; DeBrabandere H.; Waldebäck M.; Gogoll A.; Tranvik L.; Rydin E. (My University, 2007)
Phosphorus (P) binding groups were identified in phytoplankton, settling particles, and sediment profiles by 31P NMR spectroscopy from the Swedish mesotrophic Lake Erken. The 31P NMR analysis revealed that polyphosphates and pyrophosphates were abundant in the water column, but rapidly mineralized in the sediment. Orthophosphate monoesters and teichoic acids degraded more slowly than DNA-P, polyphosphates, and P lipids. Humic acids and organic acids from phytoplankton were precipitated from the NaOH extract by acidification and identified by 31P NMR spectroscopy. The precipitated P was significantly more recalcitrant than the P compound groups remaining in solution, but does not constitute a major sink of P as it did not reach a stable concentration with depth, which indicates that it may eventually be degraded. Since P also precipitated from phytoplankton, the origin of humic-P can not be related solely to allochthonous P. © 2006 Springer Science+Business Media B.V.
Keywords: 31P NMR; DEGRADATION RATES; LAKE SEDIMENT; ORGANIC P